Airway management of orofacial infections originating in the mandible - Sakkas, Andreas; Weiß, Christel; Zink, Wolfgang; Rodriguez, Camila Alejandra; Scheurer, Mario; Pietzka, Sebastian; Wilde, Frank; Thiele, Oliver Christian; Mischkowski, Robert Andreas; Ebeling, Marcel (Journal of Personalized Medicine, 2023)
The primary aim of this study was to assess the incidence of a difficult airway and emergency tracheostomy in patients with orofacial infections originating in the mandible, and a secondary aim was to determine the potential predictors of difficult intubation. This retrospective single-center study included all patients who were referred between 2015 and 2022 with an orofacial infection originating in the mandible and who were surgically drained under intubation anesthesia. The incidence of a difficult airway regarding ventilation, laryngoscopy, and intubation was analyzed descriptively. Associations between potential influencing factors and difficult intubation were examined via multivariable analysis. A total of 361 patients (mean age: 47.7 years) were included in the analysis. A difficult airway was present in 121/361 (33.5%) patients. Difficult intubation was most common in patients with infections of the massetericomandibular space (42.6%), followed by infections of the mouth floor (40%) and pterygomandibular space (23.5%). Dyspnea and stridor were not associated with the localization of infection (p = 0.6486/p = 0.4418). Multivariable analysis revealed increased age, restricted mouth opening, higher Mallampati scores, and higher Cormack-Lehane classification grades as significant predictors of difficult intubation. Higher BMI, dysphagia, dyspnea, stridor and a non-palpable mandibular rim did not influence the airway management. Patients with a difficult airway were more likely to be admitted to the ICU after surgery than patients with regular airway were (p = 0.0001). To conclude, the incidence of a difficult airway was high in patients with orofacial infections originating in the mandible. Older age, limited mouth opening, a higher Mallampati score, and a higher Cormack-Lehane grade were reliable predictors of difficult intubation.
Gesehen am 16.07.2024